Effect of Trypanosoma lewisi (Kinetoplastida: Trypanosomatidae) on the infection of white rats with Toxoplasma gondii (Eucoccidia: Sarcocystidae) oocysts - Catarinella Arrea, Gabriela (Universidad de Costa Rica, 1998)
White rats were inoculated with 10 6 trypomastigotes of Trypanosoma lewisi, simultaneously or two days before and after inoculation with 10 5 oocysts of T. gondií. A greater number of cysts was found in the brain of the animals having concomitant inoculations, as compared with rats inoculated with either one of the two parasites. An apparent immunosuppressive effec! is Iikely. Since both orgartisms can be found in rats, ít is possible that infections with T. lewisi, could make this rodent another intermediate host for Toxoplasma infections